Plasma biomarkers for predicting heart failure in patients with acute myocardial infarction - Guihong Rong; Xiao Wang; Xinling Qin; Yanxia Wang; Meilian Quan; Chunfeng Xi (Journal of Medical Biochemistry)
Background: Heart failure (HF) following acute myocardial infarction (AMI) is characterized by high mortality and disability rates, which highlights the need of timely and effective revascularization. Recent studies suggested the potential predictivity of biomarkers NT-proBNP, cTNT, PLR, NLR, and GDF-15 in cardiovascular events, but their value in HF patients post-AMI still require further verification. Therefore, the present study aimed to identify potent biomarkers for prognosticating the development of HF subsequent to AMI, and to devise early interception and therapeutic strategies. Methods: A total of 170 patients with AMI were enrolled in this study, including 44 patients with post-AMI HF and 126 patients with post-AMI non-HF. We measured the serum biomarkers NT-proBNP, cTNT, PLR, NLR, and GDF-15 in all patients using enzyme-linked immunosorbent assay (ELISA). Subsequently, we performed t-tests to assess the predictive value of these biomarkers for post-AMI HF. Results: In the group of HF patients, cTNT, NT-proBNP, GDF-15 and NLR was significantly higher than in the group without HF, but PLR was not. The AUC of NLR to predict HF after AMI was 0.632 (95%CI: 0.542-0.723), P=0.010, with a cut-off value of (3.86×109)/L, GDF-15 was 0.661 (95%CI: 0.560-0.763), P=0.002, with a cutoff value of 1.35 ng/mL, and NT-proBNP was 0.82 (95%CI: 0.723-0.876), P<0.001, with a cut-off value of 1444 pg/mL. Conclusions: In five biomarkers, there is predictive value in NT-proBNP, NLR, GDF-15 for patients with HF after AMI.